A performance measurement systems: how are they different for Malaysian SME - Nor Mahirah, Mustapha; Sorooshian, Shahryar; Noor Azlinna, Azizan (2015)
Small and Medium Enterprise play a significant role in many economies. Especially the performance of SME appeared as restructurings in many countries were implemented. This was not an exception in Malaysia. The main aim of this article is to investigate the most appropriate criteria for use in the PMS for Malaysian SME and to analyze how the Performance Measurement System (PMS) in Malaysian SME should be constructed when integrating various criteria from the past literature. The criteria of SME based on Malaysia background also will be considered in designing PMS. The necessary modification of criteria is need due to different country background. To achieve the aim the systematic literature analysis from 20 PMS model is used. The criteria they used for each model are different, and it could be not suitable with Malaysian SME, moreover even SME’s meaning also is different each countries due to several demographics factors and characteristics, and research in PMS based on Malaysia SME background is needed. The other methodologies used to achieve the objectives in this research are Delphi Technique and Decision Making Trial and Evaluation Laboratory (DEMATEL). The result found will allow to better understanding the most appropriate criteria of SME in Malaysia, also the discovery of the specific characteristics and evaluations of SME would allow easier select methods, measures and the correctness of performance measurement application to those industries in Malaysia.